2002
DOI: 10.1128/aem.68.6.2901-2909.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phenotypic, Molecular, and Virulence Characterization of Vibrio parahaemolyticus O3:K6 Isolates

Abstract: Historically, Vibrio parahaemolyticus infections have been characterized by sporadic cases caused by multiple, diverse serotypes. However, since 1996, V. parahaemolyticus serotype O3:K6 strains have been associated with several large-scale outbreaks of illness, suggesting the emergence of a "new" group of organisms with enhanced virulence. We have applied three different molecular subtyping techniques to identify an appropriate method for differentiating O3:K6 isolates from other serotypes. Pulsed-field gel el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 18 publications
2
40
0
1
Order By: Relevance
“…Isolates from Asia and the United States belonging to serotypes O3:K6, O1:KUT, and O4:K68 showed a high degree of clonality; this is consistent with previous studies (3,7,8,29,33) and supports the hypothesis of a related origin of these three new serotypes (22). However, a combination of NotI and SfiI PFGE showed slight differences between the restriction patterns from isolates belonging to the different serotypes.…”
Section: Discussionsupporting
confidence: 81%
“…Isolates from Asia and the United States belonging to serotypes O3:K6, O1:KUT, and O4:K68 showed a high degree of clonality; this is consistent with previous studies (3,7,8,29,33) and supports the hypothesis of a related origin of these three new serotypes (22). However, a combination of NotI and SfiI PFGE showed slight differences between the restriction patterns from isolates belonging to the different serotypes.…”
Section: Discussionsupporting
confidence: 81%
“…Starting with AP-PCR (17,18,57,69), a variety of molecular techniques, including ribotyping and pulsed-field gel electrophoresis (18,25,101,105), revealed that O3:K6 isolates from widely different geographic areas were genetically similar to each other and distinct from O3:K6 isolates obtained before 1995 and from non-O3:K6 serotypes. The O3:K6 isolates appearing after 1995 carried the tdh but not the trh gene, did not produce urease, and were defined by a positive group-specific PCR (GS-PCR) based on the mismatched nucleotides at seven base positions of the toxRS gene sequences and ORF8 from the f237 phage.…”
Section: Clonality Of O3:k6 Isolates and Serovariantsmentioning
confidence: 99%
“…On the other hand, the synonymous divergence between two Vibrios at other loci is similar to each other, although face values appear different due to large standard errors because of the small number of synonymous sites of each gene (Table 4). Swarming related gene In V. parahaemolyticus, it is well known that there are two types of cells, translucent (TR) and opaque (OR), of which the former has a swarming ability (Jaques and McCarter, 2006) and that the swarming ability is one of characteristics for pandemic strains (Yeung et al, 2002). Although recently three regulators of the swarming ability have been reported, results suggest the presence of additional factors of the swarming regulation in V. parahaemolyticus (Jaques and McCarter, 2006).…”
Section: Discussionmentioning
confidence: 99%